Examination of Natural Tooth Color Distribution Using Visual and Instrumental Shade Selection Methods - Nalbant A. Dilek; Babaç Yeşim Göknur; Türkcan İrem; Yerliyurt Kaan; Akçaboy Cihan; Nalbant Levent (Balkan Stomatological Society, 2016)
Aim: Although visual color determination is the most frequently applied method in dentistry, instrumental color analysis offers advantages like objectivity, measurability and rapidity. The aim of this study was to evaluate the natural teeth color in teeth without any restoration visually, and by using a computerized shade measuring and analyzing system in the population.